A Low Cost all Optical Photonic Technique Based on Brillouin Scattering for mm-Wave Generation. Issue 1 (1st August 2022) - Bansal, Mohit; Sindhwani, Manoj
Abstract: Generation of millimeter wave (mm-wave) in radio over fiber (ROF) systems is suffered from nonlinearity effects in optical fiber communication. In order to mitigate the degrading effects, a low cost all optical photonic method for the generation of mm-wave is proposed in this work. Therefore, work is accentuated on the enhanced frequency shift based on stimulated Brillouin scattering (SBS) by utilizing only one pump source. Effect of length of optical fiber, launched power and photo detector quantum efficiency is investigated over proposed architecture in order to observe power fading effects. Photonically stable, mm-wave is realized productively in the cost effective way using SBS incorporating different frequencies from 20 GHz-80 GHz. Results reveals that USB (upper sidebands) and LSB (lower sidebands) generated with demonstrated system have high power and good SNR. This makes system appropriate for radio over fiber system.